The Effectiveness of Lime Leaf Extract (Citrus aurantifolia) in Inhibiting the Growth of Staphylococcus aureus Bacteria - Budianto, Nugroho Eko Wirawan; Wahyudi, Rihan (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2026)
Herbal plants, such as lime (Citrus aurantifolia, S), have been widely used by Indonesians as traditional medicine. Limes contain beneficial compounds such as citric acid, amino acids, and essential oils. The number of samples in the study was 25, where each group consisted of 5 treatment groups. The main sample of this study was a certain strain of Staphylococcus aureus bacteria which was tested using all fresh parts of lime leaves (Citrus aurantifolia). The extract concentrations used consisted of 10%, 50%, and 90%. the positive control group (CP+) showed a significant difference compared to the negative control group (CN-) and the T1 treatment group (p=0.001), but no significant difference was observed with T2 (p=0.068) or T3 (p=0.924). The CN- group differed significantly from all other groups (p=0.001). The T1 group also demonstrated significant differences from all groups except CP+. Meanwhile, no significant differences were found between T2 and T3 (p=0.067), nor between these two groups and the positive control group (p=0.068 and p=0.924, respectively). A 90% concentration of lime leaf extract had the highest antibacterial effect against Staphylococcus aureus, followed by 50% and 10% concentrations. Further studies are needed to determine the most effective and efficient concentration Keywords: Citrus aurantifolia, lime leaves, Staphylococcus aureus, antibacterial, inhibition zone.